Assessment of the incidence of Opisthorchis felineus (Rivolta, 1884) and Metorchis bilis (Braun, 1890) infections in population of several regions of the West Siberia - Ye. N. Ilyinskikh; V. V. Novitsky; N. N. Ilyinskikh; A. V. Lepyokhin (Бюллетень сибирской медицины)
The incidence of Opisthorchis felineu s (Rivolta, 1884) and Metorchis bilis (Braun, 1890) infections among people lived in several regions of the Ob-Irtysh River basin in the West Siberia has been assessed. Our results suggest that Metorchis bilis infection was common in many of the serologically tested people. Moreover, this helminth was obtained from the biliary ducts of humans in autopsy.